Innate immune activation as cofactor in pemphigus disease manifestation - Eichkorn, Ramona A.; Schmidt, Morna F.; Walter, Elias; Hertl, Michael; Baron, Jens Malte; Waschke, Jens; Yazdi, Amir S. (Frontiers in Immunology, 2022)
Molecular mechanisms underlying autoantibody-induced acantholysis in pemphigus vulgaris are subject of current research to date. To decipher the discrepancy between ubiquitous antibody binding to the epidermal desmosomes, but discontinuous disease manifestation, we were able to identify Ultraviolet A (UVA) as a cofactor for acantholysis. UVA induces interleukin (IL)-1 secretion in keratinocytes, mirroring innate immune system activation. In an in vitro keratinocyte dissociation assay increased fragmentation was observed when UVA was added to anti-Desmoglein 3 Immunoglobulins (anti-Dsg3 IgG). These results were confirmed in skin explants where UVA enhanced anti-Dsg3-mediated loss of epidermal adhesion. The UVA-mediated effect was blocked in vitro by the pan-caspase-inhibitor zVAD-fmk. Thus, we introduce UVA as a caspase-dependent exogenous cofactor for acantholysis which suggests that local innate immune responses largely contribute to overt clinical blister formation upon autoantibody binding to epidermal cells in pemphigus vulgaris.